Local Wisdom-Based Ecotourism Development Strategy for Lolong Adventure Area, Pekalongan Regency - Firman Affandi; Sucihatiningsih Dian Wisika Prajanti; Arief Yulianto (Universitas Negeri Semarang, 2023)
The development of tourist destinations in Lolong adventure Pekalongan has several factors that support efforts development in building a tourism economy based on local wisdom, and the community can maintain local culture or wisdom. This development will have a positive impact on society such as improving the economy of communities. The regional potential is the ability of an area in the form of resources that can be used, exploited, and benefited for further development so that it is can increase and create regional capabilities. This research is descriptive qualitative research that emphasizes a field survey approach, interview, and observation, as data collection methods. Data analysis used data reduction, data triangulation, and data synthesis to reinforce the conclusions obtained. The result of this study is expected to contribute to the development of tourism, especially on local wisdom-based ecotourism on â€œLocal Wisdom-Based Ecotourism Development Strategy for Lolong Adventure Area, Pekalongan Regencyâ€. The research results show that the most prioritized criteria in the development strategy of local wisdom-based ecotourism are providing business capital assistance with a value of 0.648. The second priority is institutionalization with a weight value of 0.230, and the third criterion is human resources with a weight value of 0.122, based on the results of the Analytical Hierarchy Process (AHP) using the Expert Choice 11 program. The obtained inconsistency ratio is 0.035, which means that the answers given by the key persons are consistent. Conclusion: The results of the Analytical Hierarchy Process (AHP) calculations can be used as a basis for developing local wisdom-based ecotourism in the Lolong Adventure tourism area.